The Component Analysis of Factors Influencing the Acceptance of Robotic Process Automation in Accounting and Finance Professionals - Rojwisitphat, Aiyada; Khongmalai, Orapan (Suan Dusit Graduate School Academic Journal, 2023)
The goal of this quantitative study was to examine the components of factors influencing the acceptance of robotic process automation (RPA) in accounting and finance professionals. Purposive sampling was used to select 408 accounting and finance professionals from the automotive and parts industries in Chonburi and Rayong provinces who ever used Robotic Process Automation: RPA in their operations. An online closed-end questionnaire was used to collect data, which was then tested for content validity and reliability. Exploratory factor analysis (EFA) was used to analyze the data in order to identify common factors and create new component groups. The findings revealed that the factors influencing the acceptance of RPA software use by accounting and finance employees in the automotive and parts industries in Chonburi and Rayong provinces consisted of four factors: 1) Technology factors including complexity, relative advantage and compatibility, 2) Organizational factors including support from management, information infrastructure and training, 3) Environmental factors including threats from competition and promotion from governmental sector , and 4) Accounting competency including technology skill, problem-solving skill, adaptability skill, communication skill and morality and ethics.